The Impact of Mutation and Organizational Culture on Performance through Job Satisfaction of Hasanuddin University Employees - Marliati Marliati; Nurdjanah Hamid; Ria Mardiana Yusuf (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
This study aims to analyze; (i) the influence of work mutation variables and organizational culture on employee performance; (ii) the influence of work mutation variables and organizational culture on performance through job satisfaction; and (iii) the effect of job satisfaction variables on employee performance. The quantitative approach is used to test and analyze the factors that influence job satisfaction and employee performance. Research location at Hasanuddin University, Makassar. The population in this study were all employees who had been mutation in 2018 by 114 people. Withdrawal the number of samples in this study using saturated sampling. Data collection techniques using a questionnaire. The measurement scale used is a Likert scale with five components. Data analysis techniques in this study used path analysis. The results showed that the variable of work mutation and organizational culture had a positive and significant effect on employee performance. Work mutation variables and organizational culture have a positive and significant effect on performance through job satisfaction. Job satisfaction variable has a positive and significant effect on employee performance.